1999
DOI: 10.1136/jcp.52.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalaemic paralysis revealing Sjögren syndrome in an elderly man.

Abstract: A 73 year old white man presented with life threatening hypokalaemic paralysis requiring admission to an intensive care unit. Biochemical investigations showed severe hypokalaemia with hyperchloraemic metabolic acidosis, a spot urine pH of 6.5, and a positive urinary anion gap, establishing the diagnosis of distal renal tubular acidosis. Autoimmune tests revealed Sjögren syndrome as the underlying cause of the distal renal tubular acidosis. Full recovery followed potassium and alkali replacement. This dramatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…There are numerous case reports of primary Sjögren syndrome presenting as hypokalemic paralysis, [7][8][9] showing that overt distal RTA can precede the development of sicca complex symptoms as it did in our patient. In a retrospective study of 10 women who presented with distal RTA and urolithiasis, 8 had positive anti-SS-A titers, 7 of whom developed Sjögren syndrome at an average of 15 years of follow-up.…”
Section: Discussionsupporting
confidence: 60%
“…There are numerous case reports of primary Sjögren syndrome presenting as hypokalemic paralysis, [7][8][9] showing that overt distal RTA can precede the development of sicca complex symptoms as it did in our patient. In a retrospective study of 10 women who presented with distal RTA and urolithiasis, 8 had positive anti-SS-A titers, 7 of whom developed Sjögren syndrome at an average of 15 years of follow-up.…”
Section: Discussionsupporting
confidence: 60%
“…This case illustrates life‐threatening hypokalaemia caused by dRTA in a patient with SCLE. There are similar cases in the world literature, 2–4 some of which showed SLE/SS overlap. It has been suggested that the papulosquamous variant of SCLE, leucopenia and a high titre of autoantibodies are risk factors for the development of full‐blown SLE in those with SCLE, as illustrated by our patient.…”
Section: Discussionmentioning
confidence: 62%
“…20 Histopathology from renal biopsy specimens from these patients show evidence of an interstitial lymphocytic infiltrate with plasma cells. Although previous authors have regarded this as contributory to the tubular dysfunction, 20,25 there is not universal agreement with regards to the significance attributed to this. 22 Hypergammaglobulinaemia is often present and has been suggested as a possible pathological means of precipitating distal tubular dysfunction.…”
Section: Discussionmentioning
confidence: 89%